2012
DOI: 10.1002/bit.24563
|View full text |Cite
|
Sign up to set email alerts
|

High‐titer n‐butanol production by clostridium acetobutylicum JB200 in fed‐batch fermentation with intermittent gas stripping

Abstract: Acetone-butanol-ethanol (ABE) fermentation with a hyper-butanol producing Clostridium acetobutylicum JB200 was studied for its potential to produce a high titer of butanol that can be readily recovered with gas stripping. In batch fermentation without gas stripping, a final butanol concentration of 19.1 g/L was produced from 86.4 g/L glucose consumed in 78 h, and butanol productivity and yield were 0.24 g/L h and 0.21 g/g, respectively. In contrast, when gas stripping was applied intermittently in fed-batch fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(127 citation statements)
references
References 47 publications
4
122
1
Order By: Relevance
“…Nevertheless, it must be mentioned that gas stripping can be realised easily and that the continuous butanol removal increases the productivity [ 39 ]. Gas stripping was successfully operated in combination with batch [ 40 ], fedbatch [ 41 ], continuous [ 42 ] and fluidised bed reactors [ 43 ].…”
Section: Gas Strippingmentioning
confidence: 99%
“…Nevertheless, it must be mentioned that gas stripping can be realised easily and that the continuous butanol removal increases the productivity [ 39 ]. Gas stripping was successfully operated in combination with batch [ 40 ], fedbatch [ 41 ], continuous [ 42 ] and fluidised bed reactors [ 43 ].…”
Section: Gas Strippingmentioning
confidence: 99%
“…In addition, the low energy level due to the absence of oxidative phosphorylation often leads to a higher glycolysis rate, resulting in higher productivity (6). However, as the available ATP in anaerobic fermentation can be generated only from substrate-level phosphorylation, the biomass concentration in anaerobic fermentation is usually much lower than that in aerobic fermentation (2,7). Although a lower energy charge in anaerobic fermentation is beneficial for increasing the glycolysis rate (8)(9)(10), it has been shown that increasing the ATP concentration can improve protein synthesis and increase biomass flux during anaerobic fermentation (11,12).…”
mentioning
confidence: 99%
“…Such a highly concentrated butanol solution would significantly reduce the energy consumption required in final product recovery by distillation. 5,6 The aqueous phase contained 160.7 g/L ABE with 89.6 g/L butanol, which could be further concentrated by a second-stage PV system. 23 Productivity, yield, glucose utilization rates, and conversions achieved under the three dilution rates for a long period of continuous operation are presented in Figure 7.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…5 It is generally believed that integrating the fermentation with the product separation process by using a suitable in situ product recovery (ISPR) technique could overcome the shortage of low solvent (ABE) resistance of these strains. To date, various techniques, such as gas-stripping, pervaporation (PV), liquid−liquid extraction, and adsorption, 6 have been investigated to reduce the effect of butanol inhibition, and enhance solvent productivity and sugar utilization. Among those techniques, PV is considered to be the most promising technique because of its energy efficiency, cost effectiveness, as well as no harmful effects on the microorganisms.…”
Section: Introductionmentioning
confidence: 99%